Bibliometric Review of Sharia Fintech Studies: Focus on Innovation, Regulation, and Technology - Wasilatur Rohmah; Taufiqur Rahman (Penerbit Hellow Pustaka, 2025)
Sharia fintech has shown rapid development in line with the increasing need for financial services that are in accordance with Islamic principles. However, related literature is still scattered and has not systematically discussed aspects of innovation, regulation, and technology. This study aims to map the trend of sharia fintech research bibliometrically to identify dominant themes, collaboration patterns, and the influence of publications in this field. Data were collected from Scopus in the period 2015–2025 using related keywords and analyzed using the VOSviewer tool. The results show three main clusters: technological innovation (such as AI and blockchain), sharia financial regulation (including the role of OJK and DSN-MUI), and digital platform development. This study contributes to understanding the direction of sharia fintech development and recommends cross-aspect integration to strengthen an inclusive and sustainable sharia financial ecosystem.